The relationship between Gross Domestic Product (GDP), Interest rate and Tax rate towards Foreign direct investments in Malaysia / Nurliyana Syahirah Misbah - Misbah, Nurliyana Syahirah (2016)
The aim of this paper is to investigate the relationship of Gross Domestic Product, Interest Rate and Tax Rate towards Foreign Direct Investment in Malaysia. The data that represent the macroeconomics condition are collected was Gross Domestic Products, Interest Rate and Tax Rate (Independent variables) while Foreign Direct Investment (Dependent Variable). The data was used quarterly time series from 1997(Q1) until 2015(Q2) to analyse the significant between dependent and independent variable. The data were collected by using Thomson Reuters DataStream. Between the two models linear regression, Multiple Linear Regression Model is the best model in this study. The result display that there are positive and negative relationship between independent and dependent variable. The positive relationship is Interest Rate and negative relationship is another two variable which is Gross Domestic Product and Tax Rate towards Foreign Direct Investment. Moreover, the most influence toward Foreign Direct Investment in Malaysia is Gross Domestic Product and less influence is Interest Rate and Tax Rate. The data was analysed by using Eviews7 software and Microsoft Excel. These findings were then interpreted and explained based on the findings and several suggestions also will be discussed at the end of this study.